Why Good Things May Not Happen in Knowledge-Intensive Acquisitions: The Neglect of Acquired Firm’s Customers - William Y. Degbey (Emerald, 2022)
The primary purpose of this chapter is to offer a conceptual/theoretical understanding of post-M&A integration rationales and/or actions which pose a challenge to acquired firm customers in acquisitions of knowledge-intensive firms, and thus trigger M&A value destruction. The approach takes the form of a literature overview and conceptual development. As a step toward developing a more elaborate understanding of a customer-centered perspective, this conceptual study identifies five key factors that may lead to value leakage/destruction for acquirers’ of knowledge-intensive firms. Specifically, it identifies acquisition motive, specific acquired firm employees other than the engineers and scientists, size of the acquired firm customer-base, M&A customer compatibility, and the acquirer’s own customers’ behavior as integration rationales and/or actions which pose a challenge to acquired firm customers. In addition, the chapter offers a theoretical framework that serves as an analytical tool, and can thus be used as a foundation for future empirical work on analyzing acquirers’ destruction of value in knowledge-intensive acquisitions through the neglect of acquired firm’s customers. This study does not claim to have provided exhaustive list of all factors regarding acquirer’s integration rationales and/or actions that influence acquired firm customers. Nonetheless, for researchers seeking to build a more comprehensive framework relating to the impact of acquirer’s integration rationales and/or actions on acquired firm’s customers, this framework may serve as a solid foundation for achieving that goal. For practitioners, this study points to the importance of knowledge held by acquired firm customers and the need to maintain such customer relationships in order to avert acquirer’s post-M&A value destruction. In addition, acquirers may also recognize that post-M&A integration changes required following M&A should not be restricted to only the firm’s internal activities and resource deployment but should extend to how the firm interacts or relates with other external value creation actors. This chapter contributes by highlighting and stimulating a discussion on the important role of acquired firm customers in acquisitions of knowledge-intensive firms in informing our understanding of the sources of M&A value leakage/destruction.
Mergers and Acquisitions, Entrepreneurship and Innovation